Effect of Spinel Inversion on (CoxFe1−x)3O4 All‐Oxide Solar Cell Performance. Issue 7 (21st January 2016) - Yan, Zhi; Keller, David A.; Rietwyk, Kevin J.; Barad, Hannah‐Noa; Majhi, Koushik; Ginsburg, Adam; Anderson, Assaf Y.; Zaban, Arie
Abstract: Oxide materials have been widely investigated for use as absorber layers in high‐performance solar cells, and in this study combinatorial methods were used to specifically investigate cobalt–iron (Co–Fe) oxide composites. Structural inversion of Co–Fe oxides from a normal to an inverse spinel structure occurs at the critical composition of approximately 33 % Fe added to Co, causing changes in the crystallinity, symmetry, sub‐lattice vibrational modes, optical bandgap, and electrical resistivity. When used as an absorber layer in all‐oxide solar cells with the multi‐layered geometry of glass|FTO|TiO2 |Co–Fe–O|Au, enhanced photovoltaic performance was observed, with a maximum V oc of 534 mV at a composition of approximately 45 % Fe and a 200 % improvement in P max compared to cobalt‐rich devices. Using combinatorial data maps of the various material properties, a significant correlation between the solar cell properties and the chemical composition of the Co–Fe–O layer was revealed. This correlation allows for a better understanding of the Co–Fe–O system, which is a necessary step towards the development of Co–Fe–O‐based all‐oxide solar cells. Abstract : All Oxides, All the Time : A new absorber (Co x Fe1− x )3 O4 is synthesized for all‐oxide photovoltaics using combinatorial methods. Strong effects on the solar cell properties occur due to crystalline structure inversion (spinal to inverse spinal), which are discovered using high‐throughput techniques. This study reveals several structural and functional observations that appear to correlate with each other and open new pathways for the development of new materials and materials by design.